(untitled) (Tempo e Argumento, 2013)
This article talks about the production of the landscape of green carnaubais assuenses by means of writings of the local writers and poets. It speculates here the gamble of interest and the identity possibilities contained in elaboration of this landscape about Assu city, located in backwoods form Rio Grande do Norte. Therefore, it consists of a study that intends to contribute to the knowledge of the relations between writing, space and landscape in the place to the historical lore. Through basis theoretical of the analysis of speech from Foucault (2012), that it has the language like pragmatics and promotes actions, include being responsible for the constructions of objects of the lore and power as example of landscapes. Methodologically we operate through archaeological Foucault’s method, opportunity that discourses the writing analyzed in this article and for consequent as discursive happenings. Preliminarily, we can conclude that the carnaubais served as point of addiction to writers and poets invented an assuense identity, an identity made to mark or demarcate a space: “green carnaubais assuenses”, a construction interested because the foremen of this space/landscape aimed to supply symbolic functionality to carnaubais, already that the economic mold arising themselves appeared to evaporate. In addition, the raise of the carnaubais to conditions of local symbol translates the initiative of appropriation of a “well-vegetable” in benefit from a city.